Dietary diversity of women from soybean and non-soybean farming households in rural Zambia - Kapulu, Ndashe; Chomba, Christian; Nkonde, Chewe; Holmes, Melvin; Manda, Simon; Smith, Harriet E.; Macdiarmid, Jennie I.; Orfila, Caroline (Frontiers in Sustainable Food Systems, 2023)
Soybean farming in Zambia is promoted to increase farm productivity and diversification away from maize, and improve cash income and livelihoods for farmers. However, the impact of soybean farming on women’s dietary intake is not clear. This study compares the dietary diversity of women from soybean (S) and non-soybean (NS) farming households as a pathway to understanding policy efficacy. A cross-sectional survey involving 268 women of reproductive age from 401 rural households was conducted in two soybean-producing districts of Central Province, Zambia. Data from a qualitative 7-day food frequency questionnaire (FFQ) was used to calculate dietary diversity scores (DDS), women’s dietary diversity scores (WDDS-10) and assess dietary patterns. Information on household sociodemographic and agricultural characteristics was used to explore determinants of dietary diversity. Results show there were no significant differences in the mean DDS (S:10.3± 2.4; NS:10.3± 2.6) and WDDS-10 (S:6.27±1.55; NS:6.27±1.57) of women from soybean and non-soybean farming households. Both cohorts had similar dietary patterns, mostly plant-based food groups with additional fats and oils. Agricultural diversity was not associated with dietary diversity. Although every kilogram of crop harvested that was sold resulted in DDS increasing by 0.141, soybean farming was not statistically associated with higher wealth in this study. Household wealth status was the most important determinant of dietary diversity, as women from wealthier households were more likely to have higher DDS (β = 0.262, 95% CI = 0.26 to 0.70, P < 0.001) and WDDS-10 (β = 0.222, 95% CI = 0.08 to 0.37, P < 0.003) compared to those from poorer households. Women from households that spent more on food in the past seven days were associated with a higher DDS (β = 0.182, 95% CI = 0.002 to 0.07), but not WDDS-10 (β = 0.120, 95% CI = -0.01 to 0.03). This means that for every additional dollar spent on food in the past 7 days, the DDS increased by 0.18. Policymakers and promoters of agricultural diversification and nutrition-sensitive agriculture need to consider how women can benefit directly or indirectly from soybean farming or other interventions aimed at smallholder farmers.